The Communication Edge: Unlocking The Excellence In Public Library Services’ Delievery - Waqas Khan; Dr. Shehzad Ahmad; Dr. Sajjad Ahmad* (Dialogue Social Science Review (DSSR), 2025)
This study aims to evaluate the library services in public libraries of Khyber Pakhtunkhwa, from the point of view of communication skills of library professionals. A quantitative research design was employed to collect data from 84 librarians and 170 library users through self-designed structured questionnaire. The findings show that effective communication is much important for good service delivery; particularly written, and other verbal communication skills. Similarly, there is a significant correlation between communication skills like written and active listening with users’ satisfaction from library services. However, 45% of the library users were dissatisfied with the library services and therefore the librarian communication skills need to be improved. By implementing the study's recommendations, librarians can enhance their communication skills, adapt to the evolving role of librarianship, and ultimately improve the quality of service in public library settings, where effective communication is crucial. Keywords: Communication Skills; Effective Services Delivery; Public libraries, User Satisfaction